CBIO-02. IN VITRO TUMOR TREATING FIELDS (TTFields) REDUCE PROLIFERATION AND ALTER MLH1 EXPRESSION IN TEMOZOLOMIDE RESISTANT (TMZR) PATIENT-DERIVED GLIOBLASTOMA (GBM) CELLS. (12th November 2021) - Michelhaugh, Sharon; Degen, Katherine; Walker, Blake; Mittal, Sandeep
Abstract: BACKGROUND: TTFields therapy is approved as a monotherapy for the treatment of recurrent GBM, tumors that often have acquired resistance to TMZ. To examine TTFields efficacy in the context of TMZR in vitro, TTFields were applied to TMZR GBM cells to assess proliferation, clonogenicity, and changes in expression of O 6 -methylguanine-DNA methyltransferase (MGMT) that confers TMZ resistance and DNA Mismatch Repair Protein Mlh1 (MLH1) that may confer TMZ sensitivity. METHODS: 15-037 GBM cells were isolated from a newly-diagnosed patient tumor (IDH-WT, unmethylated MGMT promoter. Cells were grown in DMEM/F12 media with 10% FBS and gentamicin. U-251 MG cells and 15-037 cells were incubated with 100 µM TMZ for three 5-day cycles to establish TMZR. TMZR cells were plated on coverslips (1×10 4 cells/coverslip) and incubated overnight prior to TTFields application. TTFields were applied at 200 kHz (field intensity of 1.6 V/cm) for 14 days. Then coverslips (n=3/group) were harvested, counted, and replated for clonogenic assay at 1000 cells/35mm 2 well. Clonogenic assay plates were stained with crystal violet, imaged, and colonies counted. Additional coverslips (n=3/group) were harvested and MGMT and MLH1 expression were assessed by qRT-PCR with the delta-delta Ct method using GAPDH as housekeeping control. Cell counts and colony counts were compared with two-tailed t-test with significance at p < 0.05. RESULTS: In U-251 MG and 15-037 TMZR cells, TTFields application significantly reduced both cell counts and clonogenic assay colony counts compared to untreated controls (U-251 MG: 45.4% and 26.5%; 15-037: 96.2% and 60.9%, respectively, p < 0.05). In both TMZR cell lines, MGMT expression was unchanged by TTFields, but MLH1 expression increased 2.2 fold in U-251 MG cells and 7.1 fold in 15-037 cells after TTFields application. CONCLUSIONS: Not only are TMZR GBM cells sensitive to TTFields in vitro, but TTFields increased expression of MLH1 which may be able to reduce resistance to TMZ.